Concept Of Memory. Types And Processes Of Memory - Kholpulatova Mehriniso Kholpulat kizi (Euro Asian Journal Publishing, 2025)
In the article we will try to give brief information on how to improve a person’s memory and how to develop it. In order to become a perfect person, a person needs religious and world knowledge, and in order to receive so much knowledge, one must have a good memory.
Keywords: Memory; thinking; attention